Impact of State-Owned Goods Sources, State-Owned Goods, and Absorption Accounting Information Systems of State Ownershi Quality of Financial Reporting - Tri Artharini NNS Oktaviani; Cris Kuntadi (Dinasti Publisher, 2023)
In a number of research and scientific articles, the significance of prior studies or studies that are pertinent is highlighted. The idea and phenomena of bonding or intervariable impacts are bolstered by previous or pertinent research. This article employs a literature study, which is an evaluation of multiple postings about the quality of financial reports, as its methodology. The quality of financial reporting is affected by state-owned property management resources, state-owned property entrepreneurship, and the deployment of state accounting information management systems. This article's objective is to develop an intervariable effect hypothesis for use in future research. The findings of this article's literature review are as follows: 1) the resources of state property managers impact the quality of financial statements; 2) state property entrepreneurs have an impact on the Quality of Financial Statements; and 3) the application of the information management system of State property accounting impacts the quality.